Կարգալուծությունն ու շնորհի վարդապետությունն ըստ եկեղեցական իրավունքի եւ հայրաբանական ընկալման - Խմբ.՝ Առաքել Առաքելյան (1944-1948); Լևոն Կիսիբեկյան (1948-1950); Աշոտ Աբրահամյան (1950-1955); Առաքել Առաքելյան (1955-1956); Արթուն Հատիտյան (1956-1982); Պարգեւ Շահբազյան (1983-1984); Երվանդ Մելքոնյան (1985-1993); Տ. Ասողիկ եպս. Արիստակեսյան (1994-1996); Տ. Բագրատ աբղ. Գալստյան (1996-1998); Մարիամ Վարդանյան (պաշտոնակատար) (1998-1999); Տ. Արշակ աբղ. Խաչատրյան (պաշտոնակատար) (1999); Անդրանիկ Զեյթունյան (2000-2001); et al. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
The research entitled “Defrocking and the Doctrine of Grace According to the Church Law and Patristic Perception” represents canonical argumentations of defrocking, the explanation of that concept, implementation of the concept and practice of defrocking, as well as theological and patristic viewpoints on the Doctrine of Grace. Canons of "Armenian Code of Laws" - collection of Armenian ecclesiastical-legal canons - which refer to the notion of defrocking, define its reasons and circumstances, of defrocking and expelling deacons, priests, bishops from the Church hierarchy. Исследование под названием “Лишение сана и учение о благодати по церковному праву и в патристическом восприятии” представляет канонические обоснования лишения сана, дефиницию понятия, определение и применение расстрижения в разных церквах, а также богословские и патристические точки зрения на учение о благодати. Правила, касающиеся извержению из священого сана, приведенные в собрании канонов Армянского церковного права «Книге армянских канонов», определяют канонические основы и обстоятельства, причины лишения сана дьякона, иерея и епископа, лишения церковной благодати и извержения из священного сана.
Keywords: Christianity; History of the Armenian Church